Essential regulation of cell bioenergetics by constitutive InsP3 receptor Ca2+ transfer to mitochondria - Cárdenas, César; Miller, Russell A; Smith, Ian; Bui, Thi; Molgó, Jordi; Müller, Marioly; Vais, Horia; Cheung, King-Ho; Yang, Jun; Parker, Ian; Thompson, Craig B; Birnbaum, Morris J; et al. (Cell, 2010)
Mechanisms that regulate cellular metabolism are a fundamental requirement of all cells. Most eukaryotic cells rely on aerobic mitochondrial metabolism to generate ATP. Nevertheless, regulation of mitochondrial activity is incompletely understood. Here we identified an unexpected and essential role for constitutive InsP(3)R-mediated Ca(2+) release in maintaining cellular bioenergetics. Macroautophagy provides eukaryotes with an adaptive response to nutrient deprivation that prolongs survival. Constitutive InsP(3)R Ca(2+) signaling is required for macroautophagy suppression in cells in nutrient-replete media. In its absence, cells become metabolically compromised due to diminished mitochondrial Ca(2+) uptake. Mitochondrial uptake of InsP(3)R-released Ca(2+) is fundamentally required to provide optimal bioenergetics by providing sufficient reducing equivalents to support oxidative phosphorylation. Absence of this Ca(2+) transfer results in enhanced phosphorylation of pyruvate dehydrogenase and activation of AMPK, which activates prosurvival macroautophagy. Thus, constitutive InsP(3)R Ca(2+) release to mitochondria is an essential cellular process that is required for efficient mitochondrial respiration and maintenance of normal cell bioenergetics.